Kualitas Biobriket Ampas Tebu Hasil Pirolisis Sebagai Sumber Energi Alternatif - Ramadhan, Alfin; Ghazali, Anelki Amri; Maryamah, Maryamah (ALKIMIA, 2020)
At present, Indonesia needs a large energy source and the majority of energy use in Indonesia uses fossil fuels, namely fuel oil (BBM), coal, and gas. The use of fossil fuels, besides damaging the environment, is also non-renewable (nonrenewable) and unsustainable. Therefore, to anticipate environmental pollution we need another energy source that can be used by the community. In this case, biobriquette from sugarcane bagasse can be the solution because it is easy to obtain, cheap, and environmentally friendly. This study conducted 3 tests, namely: water content, heating value, and the rate of combustion where the water content testing uses a spectrameter. The samples in this study were biobriquettes with 20 g and 40 g starch adhesives, which produced the best biobriquette quality with fewer adhesives.